2009
DOI: 10.1203/pdr.0b013e3181bd5bf8
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Inhibits Candida albicans Biofilm In Vitro

Abstract: By inhibiting the conversion of 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) to mevalonate, statins impair cholesterol metabolism in humans. We reasoned that statins might similarly interfere with the biosynthesis of ergosterol, the major sterol of the yeast cell membrane. As assessed by spectrophotometric and microscopic analysis, significant inhibition of biofilm production was noted after 16-h incubation with 1, 2.5, and 5 M simvastatin, concentrations that did not affect growth, adhesion, or hyphal formation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
(42 reference statements)
2
26
0
Order By: Relevance
“…The mechanism of antifungal activity against Candida , Aspergillus spp., and Zygomycetes spp. is not clear, but it is likely to be caused by the interference of the ergosterol cycle and the disruption of the fungal cell wall. Statins also indirectly affect cell signaling , proliferation, and differentiation through inhibition of isoprenoid synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of antifungal activity against Candida , Aspergillus spp., and Zygomycetes spp. is not clear, but it is likely to be caused by the interference of the ergosterol cycle and the disruption of the fungal cell wall. Statins also indirectly affect cell signaling , proliferation, and differentiation through inhibition of isoprenoid synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these data highlight the importance of ergosterol in biofilm resistance, particularly with respect to azoles, which indirectly inhibit their biosynthesis. Recent studies have shown that simvastatin, which impairs cholesterol metabolism in humans, is capable of inhibiting C. albicans biofilms, thus providing a potential novel strategy of combating these tenacious infections [122]. …”
Section: Fungal Biofilm Resistance Mechanismsmentioning
confidence: 99%
“…Ergosterol appears to be essential for the formation of biofilms; however, as shown by Mukherjee et al[83] ergosterol levels dropped to almost half of their initial concentration after 48 hours of biofilm maturation. The importance of ergosterol for biofilm formation was shown in the study of Liu et al[84], where addition of simvastatin (a compound with inhibitory effect on ergosterol biosynthesis[85]) was reported to inhibit the formation of C. albicans biofilms. Interestingly, the effect of low simvastatin concentrations could be reversed by addition of exogenous ergosterol suggesting the importance of ergosterol in biofilm formation.…”
Section: Regulation Of Fungal Virulence By Plasma Membrane Lipidsmentioning
confidence: 99%